Teknik Penggunaan Hair Dryer sebagai Alat Pemanas pada Pengeritingan Korean Wave Perm - Meila Rahmawati; Sofia Daniati; Agus Susanti; Widiati Alifah (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2024)
Korean wave perm is the latest trend in curling hair. The price of the tools used is in the range of Rp1,000,000 to Rp5,000,000. The purpose of this research is to replace the digital perm tool with a hair dryer so that production costs can be reduced. The methods used in this research are observation, documentation, interviews, literature, questionnaires and experimental methods. Based on the assessment by 5 expert validators about the feasibility technique of using a hair dryer as a tool in curling that the technique effectiveness indicator scored 21 said to be feasible, time efficiency score 23 said to be very feasible, the cost got 21 said to be feasible, and the final result got 24 said to be very feasible. In addition, a public test was conducted to see the results of the public's level of liking for the technique of using a hair dryer as a curling tool by distributing questionnaires to 60 respondents, the results of which were 100% agreed that hair dryers could replace digital perm tools as well as save pioneering salon expenses, in the final results of the technique 55% of respondents liked it, 26.7% of respondents quite liked it and 18.3% of respondents really liked it so that 98.3% of respondents agreed that hair dryers could replace digital perm. It can be concluded that the hair dryer is feasible to use as a substitute for digital perm tools in curling korean wave perm.